TIM‐1 Signaling Is Required for Maintenance and Induction of Regulatory B Cells. Issue 4 (2nd February 2015) - Yeung, M. Y.; Ding, Q.; Brooks, C. R.; Xiao, S.; Workman, C. J.; Vignali, D. A. A.; Ueno, T.; Padera, R. F.; Kuchroo, V. K.; Najafian, N.; Rothstein, D. M.
Abstract : Apart from their role in humoral immunity, B cells can exhibit IL‐10‐dependent regulatory activity (Bregs). These regulatory subpopulations have been shown to inhibit inflammation and allograft rejection. However, our understanding of Bregs has been hampered by their rarity, lack of a specific marker, and poor insight into their induction and maintenance. We previously demonstrated that T cell immunoglobulin mucin domain‐1 (TIM‐1) identifies over 70% of IL‐10‐producing B cells, irrespective of other markers. We now show that TIM‐1 is the primary receptor responsible for Breg induction by apoptotic cells (ACs). However, B cells that express a mutant form of TIM‐1 lacking the mucin domain (TIM‐1 Δmucin ) exhibit decreased phosphatidylserine binding and are unable to produce IL‐10 in response to ACs or by specific ligation with anti‐TIM‐1. TIM‐1 Δmucin mice also exhibit accelerated allograft rejection, which appears to be due in part to their defect in both baseline and induced IL‐10 + Bregs, since a single transfer of WT TIM‐1 + B cells can restore long‐term graft survival. These data suggest that TIM‐1 signaling plays a direct role in Breg maintenance and induction both under physiological conditions (in response to ACs) and in response to therapy through TIM‐1 ligation. Moreover, they directly demonstrate that the mucin domain regulates TIM‐1 signaling. Abstract : This article demonstrates that signals through TIM‐1, an inclusive marker for regulatory B cells, are directly involved in the maintenance and induction of regulatory B cells by apoptotic cells and anti‐TIM‐1. Supplemental video content is available atamjtransplant.com .